A case of retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations - Musharaf Khan, DO; Subtain Ali, MD; Bushra Sayeed, MD; Eyassu Hailemichael, MD; Dhairya A. Lakhani, MD (Radiology Case Reports, 2025)
Retinal vasculopathy with cerebral leukoencephalopathy (RVCL) is an autosomal dominant disorder caused by mutations in the TREX1 gene, which affects medium and small arteries and veins. Reported in fewer than 50 families worldwide, RVCL typically affects individuals between 35 and 40 years of age. It commonly presents with vision disturbances due to retinal vasculopathy and neurological deficits from cerebral leukoencephalopathy. Tumefactive brain lesions are sometimes seen, which can resemble gliomas or tumefactive multiple sclerosis. RVCL is also associated with systemic manifestations, including Raynaud's phenomenon, anemia, migraines, psychological issues, and dysfunction of organs such as the kidneys, liver, gastrointestinal system, and thyroid. A positive family history is frequently noted. Early recognition of RVCL is crucial for preventing unnecessary invasive procedures, facilitating early diagnosis, and enabling family counseling. This report presents a case of RVCL-S that was initially misdiagnosed as a glioma.